A case of detection of esophageal pathology by dynamic esophagogastroscintigraphy - Lazar , Yehor; Mazur , Anastasya; Myronova , Olena; Romanenko , Hanna (The Ukrainian Scientific Medical Youth Journal, 2024)
Recently, radionuclide scintigraphy of the gastrointestinal tract has been increasingly introduced into diagnostic practice, which allows obtaining, in addition to qualitative parameters, quantitative parameters for various pathologies. In developed countries, dynamic esophagogastroscintigraphy is considered the "gold standard" for detecting functional disorders of the upper parts of the digestive tract, which cannot be obtained by other radiation methods. Insignificant radiation exposure compared to x-ray methods and non-invasiveness allows this study to be performed on patients with any pathology of the upper parts of the gastrointestinal tract. However, to date, radionuclide research of its upper parts is a scarcely available method in Ukraine, which is associated with a shortage of special equipment, radiopharmaceuticals and relevant specialists capable of correctly interpreting the obtained results. Taking into account the clinical manifestations and complaints of the patient K., 25 years old, in the radiology department of the Kyiv City Clinical Hospital No. 18, which is located on the basis of the Department of Radiology and Radiation Medicine of the National Medical University named after O.O. Bogomolets underwent dynamic esophagogastroscintigraphy. The patient did not undergo previous instrumental or radiological research methods. According to the results of the study, changes were found on the scintigraphic image of the organ, namely: the deviation of the esophagus to the left at the border of the upper and middle third, its narrowing in this area, and the retention of the radiopharmaceutical in the upper part. Quantitative changes were also observed during computer processing of the results: an increase in ETC by almost 3 times, a decrease in the clearance of the esophagus and the speed of passage of the drug through it. From the side of the stomach, a delay in the arrival of the radiopharmaceutical to it and from it to the intestine was observed. Taking into account the obtained results, to determine the cause of the specified changes, the patient was sent for further examination: fibroesophagoscopy, which revealed compressive deformation of the middle third of the esophagus, erythematous gastropathy and duodenal dyskinesia; multispiral computed tomography of the chest cavity with intravenous contrast with ultravist, which revealed a bulky formation of the posterior mediastinum, destruction of Th3, and an increase in the size of intrathoracic lymph nodes; blood test, in which neutrophilia, eosinophilia, lymphocytopenia, thrombocytopenia, normocytic anemia, increased activity of LDH and alkaline phosphatase in blood serum, increased ESR, hypergammaglobulinemia, decreased albumin level are established; trepanobiopsy of the bone marrow was performed with the detection of lymphoid cells. As a result of the additional examination, the patient was diagnosed with the classical form of Hodgkin's lymphoma - stage II lymphogranulomatosis.